Compassionate Off-Ramps: The Availability of Terminal Master's Degrees in US Medical Schools - Kristina H Petersen; Neera R Jain; Ben Case; Sharad Jain; Sarah L Solomon; Lisa M Meeks (Journal of Medical Education and Curricular Development, 2023)
Medical students who underperform or find they are not a “good fit” for medicine have limited options. A terminal master's degree represents an exit alternative that recognizes students’ completed coursework and acknowledges their commitment to the medical sciences. Although medical educators have called for the creation of such programs, termed “compassionate off-ramps,” the prevalence of degree offerings in US programs is unknown. In the fall of 2020, a survey was sent to Student Affairs Deans at 141 LCME-accredited MD programs; 73 institutions responded (52%). Terminal master's degrees were offered by 19% of respondent institutions (n = 13). While 85% of those without a terminal master's (n = 48) endorsed degree benefits, only 36% (n = 21) had plans to create the degree. This study demonstrates that few US medical schools offer a terminal master's degree, leaving students who exit medicine with high levels of debt without an avenue for a degree to support employment or future academic pursuits. The authors identify implications for students, particularly those who are at a higher risk of failing Step 1, such as students who are underrepresented in medicine, socioeconomically disadvantaged, or who have a disability and are unaccommodated. Potential barriers to terminal master's program creation are identified and mitigating strategies are recommended.